New Immigrants’ Location Choices: Magnets without Welfare - Kaushal, Neeraj (Journal of Labor Economics, 2005)
The Personal Responsibility and Work Opportunity Reconciliation Act denied legal noncitizens who arrived in the United States after August 1996 access to means‐tested federal benefits for the first 5 years. However, using state funds, a number of states restored some of the benefits. I use this state‐level policy variation to study whether newly arrived immigrants make location decisions on the basis of benefit eligibility and generosity. I find that safety‐net programs have little effect on the location choices of newly arrived low‐skilled unmarried immigrant women.